Pengembangan Instrumen Penilaian Sikap Sebagai Upaya Optimalisasi Penerapan Nilai-Nilai Yang Terkandung Dalam Akidah Akhlak Kelas VI MI DI Kulon Progo - Mujadi, Mujadi (UIN Sunan Kalijaga Yogyakarta, 2019)
Attitude competency is one of the learning outcomes that must be mastered by students in addition to knowledge and skills competencies.. It aims, if the attitude is formed early on at the next level students already have a strong character. Armed with good and strong character students will become human beings who believe and fear God Almighty, have noble character, are healthy, knowledgeable, capable, creative, independent, and become democratic and responsible citizens in accordance with national education goals.This study aims to develop assessment instruments that can be used to assess attitude competencies. This research is Sugiyono's research and development model. From the ten steps of Sugiyono's research and development, the steps taken in this study ended in the seventh step. This is due to the limitations of the author in conducting research.The results of the study indicate that the attitude assessment carried out by the teacher has not been well planned. Test the validity of experts shows the products produced from this study have a score of 3.73 with a very good category. The score was obtained from the average score given by expert assessment 3.76, material expert 3.72, Creed Morals MIN 2 teacher Kulon Progo 3.64 MI teacher Ma'arif Karangwuni 3.70, and MI Ma'arif Dondong teacher 3.83.